"I never really had the right words": Critical literacies and the collective knowledge building of girls of colour. Issue 5 (20th October 2022) - Brown, Tashal
Abstract: The questions explored in this article highlight the insights girls of colour gained through participation in a community-based organization's core course centreing examinations of power and oppression. Given that the experiences of girls of colour are often essentialized, this study highlights how their varied socio-political realities influence how they utilize curriculum and pedagogy that employs an intersectional lens to make sense of the oppressive ideologies, systems, and structures that impact the material conditions of their lives. The thoughts and perspectives shared by the girls in this study demonstrate how a curriculum that facilitates access to terminology focussed on systems of power and oppression helps them to name, understand, and draw connections to their identities and lived experiences. The girls' reflections also attest to the transformations and coalitional thinking cultivated through opportunities to engage with the diverse perspectives shared through their individual and collective narratives about their experiences with institutional, interpersonal, and internalized oppression. The knowledge and validation the girls received from their peers and faculty members strengthened their ability to critique and confront social injustice in their daily lives.